2013
DOI: 10.4028/www.scientific.net/amr.641-642.371
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research about the Application of ER Elastomer in the Shock Absorber

Abstract: When the Electrorheological elastomer (ERE) is embedded into intelligence structure system, the structure damping and stiffness of the system can be changed quickly and reversibly under an external electric field. Thus, the application of the Electrorheological elastomer in the active and passive hybrid control of structural vibration has already attracted people's wide attention. In this paper, three types of ER elastomer were prepared based on barium titanate, starch, then the microstructure of ER elastomer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16] The possibility to vary the electromechanical characteristics of EREs and their structural stability make them attractive for developing new smart materials with potential applications in the automotive industry, robotics and prosthetic limbs, vibration isolators, building applications and electro-active actuators. [17][18][19][20][21][22][23][24][25] For this purpose, ERE composites containing different inclusions and dispersed in different matrices, PANI/PDMS, 22 PbTiO 3 /AR7, 26 starch/silicone oil/silicone rubber, 27,28 polythiophene/polyisoprene, 29 Pb(Zr 0.5 ,Ti 0.5 )O 3 /acrylic rubber, 30 polydiphenylamine/poly(styrene-block-isoprene-block-styrene), 31 poly(p-phenylene)/acrylic elastomer, 32 or cellulose/BMIMCl gel, 33 have been investigated. These systems exhibited an increase of their electromechanical properties, and, in particular, of their storage modulus sensitivity {(G 0 (E) À G 0 (0))/G 0 (0)}.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] The possibility to vary the electromechanical characteristics of EREs and their structural stability make them attractive for developing new smart materials with potential applications in the automotive industry, robotics and prosthetic limbs, vibration isolators, building applications and electro-active actuators. [17][18][19][20][21][22][23][24][25] For this purpose, ERE composites containing different inclusions and dispersed in different matrices, PANI/PDMS, 22 PbTiO 3 /AR7, 26 starch/silicone oil/silicone rubber, 27,28 polythiophene/polyisoprene, 29 Pb(Zr 0.5 ,Ti 0.5 )O 3 /acrylic rubber, 30 polydiphenylamine/poly(styrene-block-isoprene-block-styrene), 31 poly(p-phenylene)/acrylic elastomer, 32 or cellulose/BMIMCl gel, 33 have been investigated. These systems exhibited an increase of their electromechanical properties, and, in particular, of their storage modulus sensitivity {(G 0 (E) À G 0 (0))/G 0 (0)}.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Electrorheological elastomers (EREs), a new kind of smart material whose stiffness varies with electric field intensity, is a competitive candidate for above problems, attracting increasing attention due to its reversible and controllable stiffness with fast response. [18][19][20] It was traditionally thought that EREs were applied to vibration attenuation or noise-reduction in aircraft, vehicles, machines, buildings, and so on [21][22][23][24][25] in shear mode.…”
Section: Smart Table Tennis Racket With Tunable Stiffness For Diverse Play Styles and Unconventional Technique Trainingmentioning
confidence: 99%
“…Since the vibration characteristics of ERE beams can be controlled by changing the strength of applied field, the EREs are useful for applications in engineering structures where variable performance is desired. In 2013, Zhu et al designed a shear mode ERE shock absorber and evaluated its vibration response performance under various excitation frequencies with and without external electric field [17]. Their experimental results showed that the stiffness and damping properties of the shock absorber could be controlled by changing the strength of applied electric field, whose macrofeatures was that the damping coefficient increased with the ascending electric field strength, and the damping effect in high frequency was better comparing with that in low frequency.…”
Section: Applications Of Eresmentioning
confidence: 99%
“…EREs also present obvious merits in comparison with magnetorheological elastomers (MREs). The EREs are driven by electric field rather than magnetic field, which is much easier to apply without the need of large-sized electromagnetic coils [15][16][17].Therefore,theEREscanbeusedtodesignsmartdeviceswithsimple structure and low weight. Due to those advantages, ER elastomers have been extensively studied in recent years and have presented promising future in applications.…”
Section: Introductionmentioning
confidence: 99%